1996
DOI: 10.1097/00006454-199612000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cytomegalovirus Infection in Infants Infected with Human Immunodeficiency Virus Type 1

Abstract: Congenital CMV infection is more common in HIV-infected infants than in HIV-uninfected infants. Infection with CMV in early life is associated with greater immunosuppression and may be associated with a more rapid progression of HIV infection in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 20 publications
8
57
1
5
Order By: Relevance
“…In this historical cohort of HIV-infected US women and their infants, we observed a 10% cCMV transmission rate (19 of 193), falling within the previously reported 2.7%-11.4% range among other ART naive, HIV-infected populations [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In this historical cohort of HIV-infected US women and their infants, we observed a 10% cCMV transmission rate (19 of 193), falling within the previously reported 2.7%-11.4% range among other ART naive, HIV-infected populations [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 56%
“…While the risk of cCMV transmission among HIV-infected women varies depending on the severity of HIV-induced immunosuppression, rates of transmission in studies conducted prior to widespread availability of antiretroviral therapy (ART) have been reported to be as high as 11% [13][14][15]. Importantly, maternal ART has been an extremely effective strategy for the reduction of in utero HIV transmission, yet the burden of cCMV infection in HIVexposed infants remains high in ART-recipient maternal populations (1.5%-3.5% transmission rate) [16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…Previous studies showed that HIV-1-infected individuals who were HCMV-seropositive progressed faster to AIDS from an average of 19 months compared with 49.5 months for HCMV-seronegative individuals. [28][29][30] Although the mechanism remains elusive, this finding suggests that HCMV infection could modulate the host in favor for HIV/AIDS. In a human cervical tissue explant model, HCMV and HIV-1 appears to coinfect macrophages, although the outcome remains unknown.…”
Section: Recent Studies Showed That Infection Of Cd34mentioning
confidence: 99%
“…Complex interactions exist between HIV and CMV, including a shared mode of in utero, perinatal, and post-natal routes of transmission [11][12][13][14]; a higher rate of congenital CMV infection in HIV-infected infants [11][12][13][14]; an impaired containment of CMV replication among HIV-infected infants [15]; and a more severe course of HIV infection, accompanied by a higher rates of central nervous system complications [16]. Mortality is also higher in CMV-HIV co-infected infants [17], and poorer growth and development had been recorded even among HIVexposed uninfected (HEU) infants who were coinfected with CMV [18].…”
Section: Introductionmentioning
confidence: 99%